Membangun Jiwa Wirausaha Di Era Digital Bagi Peserta Didik Smk Dharma Loka - Evelyn Wijaya; Yusnita Octafilia; Martha Ng; David David; Stefani Chandra; Sarli Rahman; Bord Nandre Aprila; Fery Martias (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2026)
The community service activity was held at SMK Dharma Loka Pekanbaru with the theme "Building Entrepreneurial Spirit in the Digital Era." The purpose of implementing PKM is to provide education to students on how to build an entrepreneurial spirit in the era of digitalization. The phenomenon found in the field shows that there is still limited knowledge regarding business management, lack of capital support, and low self-confidence in taking risks, which can become obstacles to the growth of entrepreneurial mentality. The PKM activity was attended by 25 students of class X at SMK Dharma Loka Pekanbaru and was conducted in the Seminar Hall of SMK Dharma Loka. The form of service in this activity includes material presentation and direct practice, followed by a discussion session and a question-and-answer session. The result of this activity is the smooth implementation of PKM and receiving positive responses from the students.